Central sensitization-related changes of effective and functional connectivity in the rat inflammatory trigeminal pain model - Spisák, Tamás; Pozsgay, Zsófia; Aranyi, Csaba; Dávid, Szabolcs; Kocsis, Pál; Nyitrai, Gabriella; Gajári, Dávid; Emri, Miklós; Czurkó, András; Kincses, Zsigmond Tamás (Neuroscience, 2017)
Central sensitization is a key mechanism in the pathology of several neuropathic pain disorders. We aimed to investigate the underlying brain connectivity changes in a rat model of chronic pain. Non-noxious whisker stimulation was used to evoke blood-oxygen-level-dependent (BOLD) responses in a block-design functional Magnetic Resonance Imaging (fMRI) experiment on 9.4T. Measurements were repeated two days and one week after injecting complete Freund's adjuvant into the rats' whisker pad. We found that acute pain reduced activation in the barrel cortex, most probably due to a plateau effect. After one week, increased activation of the anterior cingulate cortex was found. Analyses of effective connectivity driven by stimulus-related activation revealed that chronic pain-related central sensitization manifested as a widespread alteration in the activity of the somatosensory network. Changes were mainly mediated by the anterior cingulate cortex and the striatum and affected the somatosensory and motor cortices and the superior colliculus. Functional connectivity analysis of nested BOLD oscillations justified that the anterior cingular-somatosensory interplay is a key element of network changes. Additionally, a decreased cingulo-motor functional connectivity implies that alterations also involve the output tract of the network. Our results extend the knowledge about the role of the cingulate cortex in the chronification of pain and indicate that integration of multiple connectivity analysis could be fruitful in studying the central sensitization in the pain matrix.
Keywords: Animals; Magnetic Resonance Imaging; Cerebrovascular Circulation; zánět; ganglion trigeminale; central sensitization; vibrissae; Trigeminal Ganglion; Brain Mapping; mozkový krevní oběh; effective connectivity; Neural Pathways; Central Nervous System Sensitization; magnetická rezonanční tomografie; mapování mozku; nervus trigeminus; Rats, Sprague-Dawley; Inflammation; functional connectivity; Male; modely nemocí na zvířatech; potkani Sprague-Dawley; Oxygen; Trigeminal Nerve; cingulární gyrus; nervové dráhy; Disease Models, Animal; rodent pain model; chronická bolest; senzibilizace centrálního nervového systému; Chronic Pain; zvířata; mužské pohlaví; fMRI; Gyrus Cinguli; kyslík; Vibrissae